Hypotrochoidal scaffolds for cartilage regeneration - Kampen, Kenny van; Olaret, Elena; Stancu, Izabela-Cristina; Duarte Campos, Daniela Filipa; Fischer, Horst; Mota, Carlos; Moroni, Lorenzo (Materials today bio, 2023)
The main function of articular cartilage is to provide a low friction surface and protect the underlying subchondral bone. The extracellular matrix composition of articular cartilage mainly consists of glycosaminoglycans and collagen type II. Specifically, collagen type II fibers have an arch-like organization that can be mimicked with segments of a hypotrochoidal curve. In this study, a script was developed that allowed the fabrication of scaffolds with a hypotrochoidal design. This design was investigated and compared to a regular 0-90 woodpile design. The mechanical analyses revealed that the hypotrochoidal design had a lower component Young's modulus while the toughness and strain at yield were higher compared to the woodpile design. Fatigue tests showed that the hypotrochoidal design lost more energy per cycle due to the damping effect of the unique microarchitecture. In addition, data from cell culture under dynamic stimulation demonstrated that the collagen type II deposition was improved and collagen type X reduced in the hypotrochoidal design. Finally, Alcian blue staining revealed that the areas where the stress was higher during the stimulation produced more glycosaminoglycans. Our results highlight a new and simple scaffold design based on hypotrochoidal curves that could be used for cartilage tissue engineering.
Gesehen am 05.03.2024